Detection of Leukotriene Receptor CysLTR in Inflammatory Diseases by Molecular Imaging with Near-Infrared Fluorescence-Based Contrast Agents - Corinna Busch; Marta Passon; Matthias Wenzel; Ines Socher; Werner A. Kaiser; Ingrid Hilger (Molecular Imaging)
As leukotriene D 4 receptor CysLT 1 R upregulation is an early event in inflammatory processes, specific detection of CysLT 1 R via molecular imaging might be a promising diagnostic tool for inflammatory diseases. We coupled a specific anti-CysLT 1 R IgG antibody to near-infrared (NIR) hemicyanine fluorophore DY-734. The fluorophore was also coupled to unspecific rabbit-IgG antibody or corresponding Fab fragments. Expression of CysLT 1 R in HL-60 human promyelocytic leukemia cells in vitro could be proven by reverse transcriptase—polymerase chain reaction (PCR), real-time PCR, and flow cytometry. Detection of the probes by flow cytometry showed that CysLT 1 R * DY-734 probe binds distinctly stronger to HL-60 cells than IgG * DY-734. Induction of ear edema in mice was conducted to test signaling of the synthesized probes in vivo. A markedly higher fluorescence intensity was observed in the edematous region than in the healthy region by a whole-body imaging system. Semiquantitative analysis showed that CysLT 1 R * DY-734 and Fab-CysLT 1 R * DY-734 probes bind 1.9- and 1.2-fold stronger, respectively, than the unspecific probes. Biodistribution studies revealed an enrichment of full-length IgG probes in liver and spleen, whereas Fab-containing probes are mostly found in liver and kidneys. Taken together, we present an approach that might improve early diagnosis of inflammatory diseases in the long term.